THE VIOLATION OF COOPERATIVE PRINCIPLE IN SPOKEN TEST OF MEDICAL LABORATORY TECHNICIAN STUDENTS - Siti Dwi Rukmana; Annur Raidah Zahra; Zohra Amalia (English Education Department, 2018)
The paper is aimed to find out the violation of maxims occurred in spoken test of Medical Laboratory Technician. Grice cited in Yule (2006) proposed cooperative principle to control the conversation between speaker and hearer that exchange information in their talk. Grice also stated that that a participant in a talk exchange may fail to fulfil a maxim in various ways, such as violation. To gain the data, spoken test of Medical Laboratory Technician Students will be recorded. The respondent will be five students who were having spoken test. The videos were transcribed and identified which focus on the utterances that violated the maxim. Qualitative approach will be used in analyzing the data. The steps of analyzing were classifying the violation of maxims proposed by Grice found in the data, counting the violation of maxims, and analyzing the meaning of each violation. The results show that the violation of the maxim of quantity, found 6 times, is the most frequent occurrence than the other maxims. It is shown by the production of uninformative talks towards the context of the talk.